2018
DOI: 10.3389/fimmu.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Pathway Suppress Autoimmune Neuroinflammation by Inhibiting Functions of Encephalitogenic CD4 T Cells and Enhancing M2 Macrophage Polarization at the Site of Inflammation

Abstract: Although it has been demonstrated that cAMP pathway affect both adaptive and innate cell functions, the role of this pathway in the regulation of T-cell-mediated central nervous system (CNS) autoimmune inflammation, such as in experimental autoimmune encephalomyelitis (EAE), remains unclear. It is also unclear how cAMP pathway affects the function of CD4 T cells in vivo at the site of inflammation. We found that adenylyl cyclase activator Forskolin besides inhibition of functions autoimmune CD4 T cells also up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 63 publications
(115 reference statements)
3
55
0
1
Order By: Relevance
“…Apart from the above pathways related to neurodegeneration (Parkinson and Huntington disease) and metabolism (Oxidative phosphorylation) (bold/italics in Table 1), one of the eight identified MG-associated inflammatory pathways (9) showed the "counter-enrichment" pattern as well: The MacTh1 clusterassociated gene set was significantly upregulated in TAMGassociated B2 thymomas and downregulated in AB thymomas (bold/italics in Table 2). Imbalanced macrophage polarization is well-known to play an important role in T cell-and autoantibody-mediated autoimmune and allergic diseases (25)(26)(27)(28), and can affect T cell apoptosis (29), i.e., a key feature of normal thymic tolerance induction and abnormal thymopoiesis inside TAMG-associated thymomas (30). Furthermore, analyses of MHC class II expression levels and the step-wise maturation of thymocytes inside different thymoma subtypes already gave strong hints that the mechanisms shaping the autoimmune CD4+ T cell repertoire are different in AB and B2 thymomas (31).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the above pathways related to neurodegeneration (Parkinson and Huntington disease) and metabolism (Oxidative phosphorylation) (bold/italics in Table 1), one of the eight identified MG-associated inflammatory pathways (9) showed the "counter-enrichment" pattern as well: The MacTh1 clusterassociated gene set was significantly upregulated in TAMGassociated B2 thymomas and downregulated in AB thymomas (bold/italics in Table 2). Imbalanced macrophage polarization is well-known to play an important role in T cell-and autoantibody-mediated autoimmune and allergic diseases (25)(26)(27)(28), and can affect T cell apoptosis (29), i.e., a key feature of normal thymic tolerance induction and abnormal thymopoiesis inside TAMG-associated thymomas (30). Furthermore, analyses of MHC class II expression levels and the step-wise maturation of thymocytes inside different thymoma subtypes already gave strong hints that the mechanisms shaping the autoimmune CD4+ T cell repertoire are different in AB and B2 thymomas (31).…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo isolated microglia also expressed miR‐9, which was not detected in cultured adult microglia (not shown). We also investigated the expression of miR‐155, which was upregulated in classically activated M1 macrophages and often opposes the pattern of expression of miR‐124, which is expressed more in alternatively activated M2 macrophages (Ponomarev et al, ; Veremeyko et al, ). We found that NCM induced miR‐155 in YS‐, but not in BM‐derived macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Rat anti‐mouse monoclonal anti‐CD11b‐AF488 antibodies (clone M1/70) that recognize macrophages marker CD11b (Veremeyko et al, ) were purchased from BD Biosciences (0.2 mg/ml, dilution 1:100; RRID: AB_396784). Goat polyclonal anti‐human/rat/mouse antibodies for Iba1 (NP_116573.1; NP_001614.3) were purchased from BioRad (cat#AHP2024; 0.5 mg/ml, dilution 1:200; RRID: AB_2224406) and were used with secondary donkey anti‐goat IgG antibodies conjugated with AF488 (Jackson ImmunoResearch, cat#705‐546‐147, RRID: AB_2340430).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations